Neurocognitive and social-communicative function of children born very preterm at 10 years of age: Associations with microorganisms recovered from the placenta parenchyma - Tomlinson, Martha Scott (J Perinatol, 2019)
OBJECTIVE: Infection of the placenta has been associated with preterm birth as well as neurocognitive impairment. This study aimed to determine whether specific bacterial species in the placenta of extremely preterm pregnancies are associated with neurological deficits later in life. STUDY DESIGN: Using data from 807 children in the ELGAN study the risks of a low score on six neurological assessments in relation to 15 different microbes were quantified with odds ratios. RESULTS: The presence of certain microbial species in the placenta was associated with lower scores on numerical and oral language assessments. Lactobacillus sp. was associated with decreased risk of a low oral language score and a composite measure of IQ and executive function. CONCLUSION: Placental microorganisms were associated with neurocognitive, but not social-communicative, outcomes at age 10. In contrast, the presence of the anti-inflammatory Lactobacillus sp. in the placenta was associated with a lower risk of impaired neurocognitive functions.